John Stuart Mill and epistemic democracy - Cerovac, Ivan, 1946- (Lexington Books, 2022)
"This book characterizes Mill as a political instrumentalist and an epistemic democrat, analyzing the epistemic arguments he uses to support his political proposals. Exploring his endeavor to resolve the conflict between political and epistemic values, it sets the epistemic criteria as a basis for unifying Mill's political thought"--